BEZIT AND NARCOTICS POWER ACCORDING TO LAW NO. 35 OF 2009 CONCERNING NARCOTICS - Ahmad Hunaeni Zulkarnaen (Jurnal Hukum Mimbar Justitia, 2018)
Narcotics are substances or drugs that have the potential to damage health, which then production, distribution and consumption are then regulated in code No. 35 of 2009 concerning Narcotics (UUN). Drug abuse is the act of possessing, buying, selling and using narcotics. Narcotics abuses are considered to be high-level crime (extraordinary crime), and the sanctions for such crimes are very serious, starting from rehabilitation to capital punishment. seeing the severity of sanctions on narcotics abusers and the unclear definition of "possessing" in UUN, of course legal protection of suspected drug abusers must be taken seriously. Especially for those possessing/carrying narcotics without their knowledge.Â Keywords: Bezit; Narcotics; Drug Abuse.